2020
DOI: 10.1002/lrh2.10226
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐level analysis of the learning health system: Integrating contributions from research on organizations and implementation

Abstract: Introduction: Organizations and systems that deliver health care may better adapt to rapid change in their environments by acting as learning organizations and learning health systems (LHSs). Despite widespread recognition that multilevel forces shape capacity for learning within care delivery organizations, there is no agreed-on, comprehensive, multilevel framework to inform LHS research and practice. Methods:We develop such a framework, which can enhance both research on LHSs and practical steps toward their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 68 publications
3
54
0
Order By: Relevance
“…Rather, our model focuses on critical elements central to an LHS's functioning and could be used in complement with an ecologically or organizationally focused model, such as the multilevel framework of factors influencing organizational learning. 15 Finally, given our program's state of development we do not yet have outcome measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, our model focuses on critical elements central to an LHS's functioning and could be used in complement with an ecologically or organizationally focused model, such as the multilevel framework of factors influencing organizational learning. 15 Finally, given our program's state of development we do not yet have outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“…While numerous papers list the desired constructs (fundamental components) of an LHS, details about how to operationalize those constructs, maximize the relationships among them, and assess their effectiveness and impact are lacking. 13 , 14 , 15 A systematic review of LHS programs concluded that most work has been conceptual and unapplied, with “minimal focus on evaluating the impact.” 16 Demonstrating the impact of an LHS could be a catalyst to higher acceptance and adoption of LHS concepts by health systems worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…This work echoes prior work by Harrison and Shortell (2020) that describes the functions and inter-workings of the LHS, emphasizing the importance of a system-level approach that facilitates "deep learning" 1 across layers of the organization and ensuring that innovations such as ePROs align with system incentives, leadership goals, and available infrastructure to support data and knowledge management. 1,5 For example, one of our guidelines related to the theme of governance recommends identifying an IT strategy for ePRO use that considers the technology used, approach to electronic health record (EHR) integration, and management of IT resources and standards.…”
Section: Guideline Theme 3: Reportingmentioning
confidence: 99%
“…Capturing data from patients through patient-reported outcomes is an emerging aspect of healthcare delivery and aligns with the core objectives of a learning health system (LHS). [1][2][3] As articulated by Friedman and others, an LHS aligns data, technology, and care delivery to generate and apply evidence to practice in a continuous cycle to advance care. 4,5 A central tenant of an LHS is harnessing the power of data in ways that empower and engage patients and care teams with the knowledge to provide the best care for each patient.…”
Section: Introductionmentioning
confidence: 99%
“…We propose that the key mechanism of a learning organization is true alignment and empowerment of stakeholders at both the organizational and clinician levels to continuously use the most relevant data at each levelincluding feedback from consumers-to engender clinical practice and organizational change (see figure in the online supplement) (9).…”
Section: What Is a Learning Organization?mentioning
confidence: 99%